Temporal Artery Compression Sign – A Novel Ultrasound Finding for the Diagnosis of Giant Cell Arteritis - Aschwanden, M.; Daikeler, T.; Kesten, F.; Baldi, T.; Benz, D.; Tyndall, A.; Imfeld, S.; Staub, D.; Hess, C.; Jaeger, K. A. (Ultraschall in der Medizin - European Journal of Ultrasound, 2013)
Purpose: In patients with suspected giant cell arteritis (GCA), a search for the perivascular halo sign, a sophisticated color duplex ultrasound (CDU) finding, at experienced centers reliably identifies inflamed temporal arteries (TA). We tested whether TA compression in patients with GCA, a simple, largely operator-independent maneuver, elicits contrasting echogenicity between the diseased artery wall and the surrounding tissue (compression sign). Materials and Methods: 80 individuals with suspected GCA were prospectively enrolled in this single-center study. In all study participants, bilateral ultrasound examination of the TA established the presence/absence of the halo and compression sign. A positive compression sign was defined as visibility of the TA upon transducer-imposed compression of the artery. Based on ACR criteria, a team of specialized physicians independently grouped patients as GCA versus non-GCA. Results: 43/80 study participants were grouped as GCA. Both the halo sign and the compression sign were positive in 34/43 patients in the GCA group, and negative in all 37/37 of the non-GCA group, resulting in a sensitivity of 79 % and a specificity of 100 % for both the halo and the compression sign. Conclusion: In this cohort of individuals with suspected GCA, the halo sign and the compression sign were equal in their diagnostic performance. The simplicity of the compression sign suggests a level of reliability warranting further evaluation.
Keywords: vascular; ultrasound color Doppler; vasculitis; temporal artery